Development of the web-based nutrition information system “SehatMate” for adolescents and adults using the agile method - Putri Liana Suryadi; Fitrianingsih Fitrianingsih; Lestari Octavia (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2026)
Nutrition literacy and tools for calculating individual energy needs remain limited among adolescents and adults, potentially hindering balanced diet implementation in daily life. This study aims to develop SehatMate, a web-based nutrition system integrating Basal Metabolic Rate (BMR) and Total Daily Energy Expenditure (TDEE) calculations with dietary recording and a food composition database. An Agile software engineering approach was used with iterative planning, UML-based design, web framework and MySQL implementation, followed by testing, documentation, and deployment. BMR is calculated using the Harris–Benedict equation, while TDEE is derived from an activity factor. Food composition data from the Indonesian Food Composition Table were integrated into the system. System validation included comparison with manual calculations and black-box testing of user and admin functions across devices and browsers. The results show that SehatMate provides modules for registration, profile management, energy requirement calculation, food selection, daily intake recording, and nutrient adequacy recap. Findings indicate that system-generated BMR and TDEE values are consistent with manual calculations, and functional testing confirms system reliability across platforms. In conclusion, the system meets functional requirements for supporting nutrition education and dietary planning; however, further development is required to expand the nutrient database, improve personalization, and evaluate usability in real-user settings.